2017
DOI: 10.1007/s00192-017-3362-z
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, nonblinded extension study of single-incision versus transobturator midurethral sling in women with stress urinary incontinence

Abstract: After a follow-up of 36 months, MiniArc (SIMS) is non-inferior to Monarc (SMUS) with respect to subjective and objective cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Few studies have reported medium-term outcomes of SIMS. [25][26][27] Overall, the various analyses of our trial demonstrated that objective cure of SUI favored TOT over a SIMS technique in the medium-term. Considering only the participants who completed 3-year follow-up which would best reproduce the treatment differences, cure reached 90.2% for TOT confirming the high success rate for MUS described by literature [21][22][23][24] while SIMS reached 68.3%.…”
Section: Discussionmentioning
confidence: 64%
“…Few studies have reported medium-term outcomes of SIMS. [25][26][27] Overall, the various analyses of our trial demonstrated that objective cure of SUI favored TOT over a SIMS technique in the medium-term. Considering only the participants who completed 3-year follow-up which would best reproduce the treatment differences, cure reached 90.2% for TOT confirming the high success rate for MUS described by literature [21][22][23][24] while SIMS reached 68.3%.…”
Section: Discussionmentioning
confidence: 64%
“…Data searches were performed in Google Scholar, PubMed, Medline, Embase, Scopus, Web of Science and the Cochrane Database of Systematic Reviews. Finally, 29 studies , including a total of 2 986 women, were selected for the meta‐analysis. An SIMS was defined as a midurethral sling placed through a single vaginal incision without skin incision, and included the Mini‐Arc, Contasure‐Needleless, Ophira, tissue fixation system (TFS) and Ajust.…”
Section: Methodsmentioning
confidence: 99%
“…Basu and Duckett , Schellart et al , Masata et al and Oliveira et al , published papers with in the same cohort of patients in different follow‐up years. In these cases, only objective and subjective cure rates were extracted from each paper for subgroup analysis based on the follow‐up period (Figs C and C).…”
Section: Methodsmentioning
confidence: 99%
“…SIMS are less invasive compared to SMUS and can therefore more easily be performed in an outpatient setting under local analgesia. Moreover, although SIMS are very different from each other, some have been evaluated in randomized controlled trials and shown to be associated with shorter operative time, less postoperative pain yet, and noninferior cure rates of 85% in comparison to transobturator tapes (TOT) …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although SIMS are very different from each other, some have been evaluated in randomized controlled trials and shown to be associated with shorter operative time, less postoperative pain yet, and noninferior cure rates of 85% in comparison to transobturator tapes (TOT). 2,3 Urethral bulking agents (UBA) are an alternative option to treat SUI and can be performed in an outpatient setting using local analgesia. This can be seen as potentially beneficial to patients compared to MUS surgery.…”
Section: Introductionmentioning
confidence: 99%